Application of critical discourse analysis in media discourse studies - Ramanathan, Renugah; Tan, Bee Hoon (Penerbit Universiti Kebangsaan Malaysia, 2015)
The critical period in discourse analysis emerged between the late 1990s and early 2000s in the field of applied linguistics drawing upon a variety of analytical frameworks and approaches. The purpose of this review is to find out how CDA plays a vital role in unravelling the hidden ideologies while scrutinizing the presence of power in media discourse studies. This study reviewed fifteen journal articles to examine the ways and methods in which CDA has been used to discover the social phenomenon while revealing the authentic identity of the social actors. It was found that CDA has been utilised widely to unmask the ideologies which discriminate the oppressed group while presenting a positive image for the group with the highest authority.